Evaluation of bait flavors for potential use in oral rabies vaccine delivery to feral dogs (Canis familiaris) - Bender, S. C.; Bender, P.; Hausig, K.; Berentsen, A.; Bergman, D. L.; VerCauteren, K. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Texto em inglês